Double‐Stranded Helical Oligomers Covalently Bridged by Rotary Cyclic Boronate Esters. Issue 8 (14th March 2017) - Iida, Hiroki; Ohmura, Kenji; Noda, Ryuta; Iwahana, Soichiro; Katagiri, Hiroshi; Ousaka, Naoki; Hayashi, Taku; Hijikata, Yuh; Irle, Stephan; Yashima, Eiji
Abstract: Novel double helices covalently bridged by cyclic boronate esters were synthesized from complementary dimers with an m ‐terphenyl backbone joined by a chiral or achiral phenylene linker bearing diethyl boronates and diols, respectively. The X‐ray crystallographic analysis and variable‐temperature NMR and circular dichroism measurements, along with theoretical calculations, revealed that the double helices function as a "molecular rotor" in which the cyclic boronate ester units rotate, yielding two stable rotamers at low temperatures. Moreover, our data indicates that the covalently bonded double helices can undergo a unique helix‐inversion simultaneously with a rotational motion of the boronate esters. Abstract : The helices are in motion : Novel double‐stranded helices covalently bridged by two cyclic boronate esters were prepared by simply mixing two complementary dimer strands bearing diethyl boronates and diols. A rotational motion of the encased cyclic boronate ester units can take place simultaneously with helix‐inversion of the double‐stranded helical framework, thus providing a unique molecular rotor that undergoes dual rotary and inverting (twisting) motions.